The decision making index on culling cows in Iran - Chizari, Ali (2013)
Agriculture is a competitive industry which means that economic profits will be close to zero in the long run and farmers in agricultural sector need to be agile so as the profit of their agricultural activities need to be maintained. Therefore, effort needs to focus on approaches to maintain profit and the performance of the individual dairy animal in term of milk yield over the period. One of the main decision-making in the dairy farm is;whether to cull or not to cull the animal based on the individual performance especially on milk yield and the overall performance of the farm. This decision-making by farmers or managers on keeping or culling cow is a complex and controversial one. However,the main target for every plan whether to cull or to keep is to improved profitability for now and in the future. Cows exist in the herds based on different reasons and dairy cows will be eventually cull but the time for each cow is specific and it has a direct impact on the animal and farm profitability. Thus culling on time and replacing precisely help to develop herd profitability. On the other aspect, selling heifers as an important resource of providing cash for dairy herds and thus harmony and balance between culling cows,replacing and selling heifers call cull-replace strategy to approach the sustainable profit in future. There are four ways to increase profitability on the dairy herd: 1) decreasing cost of production; 2) decreasing assets per unit of producer (dairy cow) ; 3) increasing production; 4) finding the best market with a good price. According to these paths,decreasing cost without attention to the assets per unit of producers is not strong and stable way to generate profit at the farm. The aim of this study demonstrate that, one of the ways to compute of profitability is return on assets (ROA) which shows the ratio of profit with compare the amount of assets and net revenue. This is obtaining by using the culling-replacement decision and the expected ROA generated for such decision compare to business as usual scenario. A dairy business has three stages as illustrated that are input, process and output. The most important stage is input which has three steps; Basic (Land and Labor), Purchase Capital (Cow, Machinery and Building) and Intermediate (Services and Feeding). Furthermore, cow as an important purchase capital included approximately 33 percent of the total assets on the farm which needs to renew every year because of cull-replace strategy to keep and protect profit at the farm. Productivity and efficiency are second reason to use ROA in this study. Efficiency refers to costs and operating profit margin reflects the efficiency of the operation. Productivity relates to a dairy farm’s success in generating output (milk, calf) employing a given set of resources (assets) and the assets turnover ratio reflects the farm’s productivity. Thus,herd managers ought to range and balance stability between efficiency and productivity to accomplish herd profit. Dairy producers can use two financial measures to assess the productivity and efficiency of their dairy farm business. It means that when considered these two together (based on formulation) the result is return on assets (ROA). On the other hand, using ROA is involved assets turnover ratio as productivity and operating profit margin as efficiency simultaneously. This explanation clearly shows that dairy producers should not focus their attention solely on cutting cost in order to improve efficiency. The drive for greater efficiency can raise profits, but it also can have the opposite effect when cost cutting results in big declines in productivity. Producers must be aware of the trade-off between productivity (turnings) and efficiency (earnings) as they consider cost-cutting measures. The computation of profitability is crucial in order to evaluate of assets at differences price between cow and heifer and also different performance in production and operating cost between them. In addition, the cull-replace strategy will also include the amount of the animal assets that will affect the profitability ratio and finally to make culling decision. The model of most studies based on finding profitability of individual cows in the herd. According to the conceptual framework and variables that need to consider in this study,return on assets (ROA) has selected as a model to estimate a cow’s performance. As explained in the previous paragraphs, procedures of profitability are extensive and based on objectives and available information. Profitability ratios reveal the degree of success or failure over a given period. On the other hand, it is necessary to understand whether the business is spending money efficiently toward making profits or not. About six methods normally being use to analyze the financial performance of a dairy farm. Value of production, net income from operation, net income, and operating profit margin are four methods, which only judge income and cost. In order to compute cow return on assets milk revenue and pregnancy value as an income and feed cost, mastitis cost, lameness cost, replacement cost, days open cost and breeding cost as a cost and cow assets as an assets have considered. The results of expenditures are very considerable because, in all past studies most authors focus on feed and days open cost. In our case six other costs were included such as feed cost, breeding cost, mastitis, lameness, days open cost and replacement cost. The result indicates that, feed cost as an important operating cost is in the first place by 51.88 percent (USD1,231.83 average per cow annually) follows by days open cost at 24.31 percent (USD577.22 average per cow annually), replacement cost at 11.72 percent (USD266.48 average per cow annually), breeding, lameness and mastitis cost at 6.33, 4.41and 1.84 percent with USD150.24, USD104.74 and USD43.69 respectively. Thus this study shows that more than 40 percent (41.79 percent about USD992.14) of the operating cost belongs to the hidden or implicit costs which normally not being considered when computing using financial method. As results, without attention to this main part of costs our decision to cull-replace program will be misleading and the farmers can make a wrong decision. The result of days open cost shows that on average the daily days open cost is USD3.852 on per cow annually. Similarly USD94.07 per cow annually was charged to total days open cost due to delay in pregnancy on culling the cows (16.30 percent). The quality of cull cows also show that optimization of ROA is much precisely rather than net revenue (NR). Regardless of all changes or the strategy used, there is the need to figure out the quality of the herd. Even though, all variables have a connection with each other, but it is better to evaluate them separately. Regarding the output cows results,the yield of cull cows in the Optimization (OP) is lower than Net Income (NI) index. By relying on the results, in OP, there are selected high days in milk (240 days), and low Mature Equivalent (ME) milk production (8173 kg) and high number of services (2.9 times) as compare to NI (223 days for Days in Milk (DIM)), 8825 kg ME milk, 2.5 times of services). Furthermore, somatic cell count (SCC), Lameness (locomotion score), and days open in OP strategy are higher than other ways compare to Net Income (187 SCC, 2.3 Lameness, and 184 Days Open, thus with this program (OP), low performance cow can be a candidate to be cull as well. This study shows that in order to make decision to cull-replace strategy for dairy cows we need to consider main implicit costs such as days open cost, replacement cost, mastitis cost, lameness cost that involved about 40 percent of total cost. Next, to figure out the best performance of the cows and heifers should consider the animal assets. Finally, results demonstrate that with optimization future return on assets can find the best decision to cull and future profit.